Mesoscopic shear behavior and strength characteristic of UHPC-NC interface considering the combined effect of mechanical interlocking and dowel action - Yang, Jun; Xia, Junrun; Zhang, Zhongya; Zhou, Jianting; Zou, Yang; Wang, Yanshuai; Shen, Xiujiang (Engineering fracture mechanics, 2024)
•The mesoscopic shear behaviors of the UHPC-NC interface were studied by using the DIC technique.•The combined effect of aggregate interlocking and dowel action on the interfacial properties were revealed.•The existing shear-friction coefficients in literature and dowel action model were evaluated. Mechanical interlocking and dowel action are crucial factors influencing the interfacial shear resistance between ultra-high performance concrete (UHPC) and normal concrete (NC). Despite the individual role of mechanical interlocking and dowel action in restricting slip between UHPC and NC, the combined behavior of them remains to be explored due to the complexity of interface transition zone (ITZ) contact. To this end, this study investigates the shear behavior of UHPC-NC interface considering various types of mechanical interlocking (smooth, with aggregate or shear key interlocking) and different shear reinforcement ratios. Using digital correlation image (DIC) technique, the contribution of mechanical interlocking and dowel action on the mesoscopic crack propagation of UHPC-NC interface were revealed. Eventually, the shear models of UHPC-NC interface considering the combined effects were compared with existing shear models in the literature and codes comprehensively. Results indicate that the combined effect of mechanical interlocking and dowel action can effectively restrict the crack propagation in the ITZ, thus improving the shear resistance of UHPC-NC interface. Dowel action can significantly enhance the shear strength of the UHPC-NC interface with castellated key, but its impact on increasing the capacity of rough interfaces is not as pronounced. Specifically, when the interface reinforcement ratio increased from 0 % to 0.39 %, the enhancement in the shear strength of rough interface was only 2.4 %, while for the interface with castellated key, the enhancement in the shear strength was 110.9 %. To quantify the reduction in shear contribution of dowel action due to the enhanced aggregate interlocking behavior, a model was established based on the fib code.